2016
DOI: 10.1172/jci83669
|View full text |Cite|
|
Sign up to set email alerts
|

NLRP3 tyrosine phosphorylation is controlled by protein tyrosine phosphatase PTPN22

Abstract: were inadvertently omitted from the author list. The correct author and affiliations list is above. The updated author contributions section is below.MRS performed experiments, analyzed the data, and wrote the first draft of the manuscript. SK, CG, TR, IFW, SL, KA, and WF performed experiments and were involved in data analysis. PMG and MGG were involved in vector design and subcloning. DJR and XD generated PTPN22-619W mice. HDB and EC performed experiments in keratinocytes and were involved in data analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
146
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(151 citation statements)
references
References 53 publications
(89 reference statements)
3
146
1
1
Order By: Relevance
“…Thus, Stutz et al and Mortimer et al reported that dephosphorylation of serine (S5 or S295) is necessary for NLRP3 activation, whereas Spalinger et al reported that dephosphorylation of a tyrosine (Y861) has this function (13,38,39). It was therefore logical to assume that CARD8 regulates NLRP3 inflammasome by affecting NLRP3 dephosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Stutz et al and Mortimer et al reported that dephosphorylation of serine (S5 or S295) is necessary for NLRP3 activation, whereas Spalinger et al reported that dephosphorylation of a tyrosine (Y861) has this function (13,38,39). It was therefore logical to assume that CARD8 regulates NLRP3 inflammasome by affecting NLRP3 dephosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impaired expression of ATM and PFKFB3, which are also induced by anti-CD3 stimulation, in ARI PBMCs cannot be explained by stronger activation signals and suggests a novel mechanism. The phosphatase activity of PTPN22 also inhibits the signals induced by type I interferon (49), modulates macrophage polarization (50), and activates the inflammasome by dephosphorylating NLRP3 (51). A role of NLRP3 in Th cells was recently discovered (52).…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB pathway. Signal 1-induced deubiquitination and dephosphorylation of NLRP3 by BRCC3 and PTPN22, respectively, have been proposed to be necessary for the licensing of NLRP3 [125,126] , and Ca 2+ -sensitive cAMP has been shown to act as an intracellular inhibitor of NLRP3 [127] . The second signal is less defined, but involves potassium efflux, calcium mobilization from intracellular store compartments, and the production of ROS [124] .…”
Section: Inflammasomes and The Activation Of Innate Immunitymentioning
confidence: 99%